Positive Self-Relation Scale - development and psychometric properties - Ociskova, Marie; Prasko, Jan; Kupka, Martin (Psychology research and behavior management, 2019)
PURPOSE: Self-relation is a profound connection that influences one's life. As such, it presents an important topic for various areas of research and psychotherapy. The goal of this study was to develop and evaluate a brief scale that would assess positive aspects of self-relation. SAMPLE AND METHODS: The Positive Self-Relation Scale (PSRS) consists of 16 items divided into 4 subscales - Self-Acceptance, Self-Confidence, Authenticity and Assertiveness, and Fulfilled Experience. Two samples were used for the evaluation of its content and factor structure. The final sample's data used for validation assessment. This sample consisted of 1234 adults from a general population (mean age 34.8±14.2 years, 70.8% women). All participants completed PSRS. Subgroups also filled in Rosenberg Self-Esteem Scale (RSES), Adult Dispositional Hope Scale (ADHS), Beck Depression Inventory-II (BDI-II), Liebowitz Social Anxiety Scale (LSAS), and Dissociative Experiences Scale (DES). RESULTS: Differences in scores among demographic groups were small to none. Internal consistency was good (Composite Reliability Coefficients - the whole scale: 0.93; the subscales: 0.73-0.80). Temporal stability, assessed 2 weeks apart, was satisfactory (intraclass correlation coefficients - the whole scale: 0.86, the subscales: 0.60-0.82). Factor loadings in confirmatory factor analysis were 0.45-0.80, fit indices mostly showed an adequate model. The correlation coefficients between PSRS and RSES/ADHS were strong (r=0.79/0.55). The scale also strongly correlated with LSAS, BDI-II, and DES (r=-0.61/-0.48/-0.30, all ps<0.001). CONCLUSION: PSRS showed adequate psychometric properties in the general population. Future studies should include clinical samples. The areas of application lie mainly in research and psychotherapy.
Keywords: self-relation; self-esteem; psychometric properties; self-acceptance; positive psychology